New Macedonian Photography? : (round table). - Abadzieva, Sonja; Avramovska, Elizabeta; Benjamin, Walter; Budievac, Dejan; Deleva, Ljupka; Dimitrovski, Valentino; Dimovski, Krume; Dzeparoski, Ivan; Gavrovski, Cvetan; Hristova, Liljana; Ivanov, Bojan; Jankuloski, Robert; et al. (Skopje : SCCA (Soros Center for Contemporary Arts), 1999)
Vilic, Nebojsa ; Avramovska, Elizabeta ; Abadzieva, Sonja ; Dimitrovski, Valentino ; Plavevski, Lazo ; Gavrovski, Cvetan ; Jankuloski, Robert ; Ivanov, Bojan ; Dzeparoski, Ivan ; Dimovski, Krume ; Ivanov, Bojan ; Deleva, Ljupka
Engels & Macedonisch
boek
Keywords: Macedonië